The Effectiveness Of The Long-Term Acrylic Resin Plate Immersion In Various Concentrations Of Black Tea On Color Change Difference - Soebagio; Yogiartono, R. Moh. (International Journal of Psychosocial Rehabilitation, 2020)
Background: Dentures are generally made of a heat-cured type polymethyl methacrylate acrylic resins. Acrylic resin has the property to absorb water slowly over a period of time by absorbing it through the diffusion of water molecules and experiencing water saturation within 17 days. Polyphenols that come in contact with acrylic resin plates will react with esters of polymethyl metacrylate in acrylic resins to form brown colored coatings that are attached to the surface of the acrylic resin plates. Purpose: Candida albicans colonies of the acrylic resin plate in long-term black tea immersion. Materials and Methods: Black tea, which contains antibacterial and fungicidal properties, can reduce Candida albicans attached to the surface of acrylic resin plates. In this study, acrylic resin plates immersed in a black tea with a concentration of 10 grams, 20 grams and 40 grams in 300 ml of water for 1 hour, 4 hours and 8 hours turned out to be a decrease in transverse strength and there was a thickening of the brown colored layer that attaches to the resin plate acrylic with strong curls. Result: Statistical tests show that there are significant differences between each group of transverse strengths and thickness of the layers. Conclusions: The more concentrated the concentration of black tea brewing and the longer the acrylic plate is immersed in the brewing of black tea